Analisis Perbedaan Peformance dan Quality Of Service (Qos) Antara Eigrp dengan Ospf (Studi Kasus Menggunakan 6 Router Melalui GNS 3 dan Wireshark) - Verawardina, Unung (International Journal of Natural Science and Engineering, 2018)
In a dynamic routing setting a routing protocol is required to perform the settings to find the shortest and best path. Routing protocols are of two types: vector distance and link state. Use of EIGRP routing that includes long-range vectors and link state OSPF Link link state coverage, peg well to be implemented in complex network because it can adapt well. In this research is the method used for routing and speed of time available EIGRP routing and OSPF routing through simulator GNS3 and wireshark application, then analyze the difference of peformance with speed of routing table and speed of time. While for Quality of Service (QoS) compare network service quality from EIGRP and OSPF routing which include delay, packet loss, and throughput. Based on the results of the research shows the EIGRP routing table is better in the selection path, EIGRP smaller time tansfer data then its data transfer faster than the OSPF. Overall Quality Of Service (Qos) delay, packetloss and throughput on EIGRP and OSPF are well balanced and good.